PENERAPAN MODEL PROJECT BASED LEARNING MELALUI PENDEKATAN STUDENT-CENTERED LEARNING DALAM PEMBELAJARAN TEKS PROSEDUR PADA SISWA KELAS VII - Yusnidar Giawa; Christin Agustina Purba; Johannes Simamora (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aimed to describe the implementation of the Project Based Learning (PjBL) model within the Student Centered Learning (SCL) approach in procedural text learning for seventh-grade students at SMP Kemala Bhayangkari 1 Medan, to describe students’ activeness during the learning process, and to analyze students’ ability in writing procedural texts after the implementation of the model. This research was motivated by the low level of student participation and the less optimal ability of students in composing procedural texts systematically and according to appropriate linguistic rules. This study employed a descriptive method with a qualitative approach. The research data were obtained through observation, interviews, and documentation. The results of the study showed that the implementation of the Project Based Learning model within the Student Centered Learning approach was carried out effectively and was able to create an active, collaborative, and meaningful learning environment. Students’ activeness increased, as indicated by their participation in discussions, group collaboration, confidence in expressing opinions, and involvement in project activities. In addition, students’ ability in writing procedural texts also improved, particularly in terms of text structure, linguistic features, sequence of steps, and clarity of the text content. This improvement occurred because students gained direct learning experiences through project-based activities, making it easier for them to understand the learning material. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan penerapan model Project Based Learning (PjBL) dalam pendekatan Student Centered Learning (SCL) pada pembelajaran teks prosedur siswa kelas VII SMP Kemala Bhayangkari 1 Medan, mendeskripsikan keaktifan siswa selama proses pembelajaran, serta menganalisis kemampuan siswa dalam menyusun teks prosedur setelah penerapan model tersebut. Penelitian ini dilatarbelakangi oleh rendahnya keaktifan siswa dan kurang optimalnya kemampuan siswa dalam menyusun teks prosedur secara sistematis dan sesuai kaidah kebahasaan. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Data penelitian diperoleh melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan model Project Based Learning dalam pendekatan Student Centered Learning terlaksana dengan baik dan mampu menciptakan pembelajaran yang aktif, kolaboratif, dan bermakna. Keaktifan siswa mengalami peningkatan yang terlihat dari partisipasi siswa dalam diskusi, kerja sama kelompok, keberanian menyampaikan pendapat, serta keterlibatan dalam pelaksanaan proyek. Selain itu, kemampuan siswa dalam menyusun teks prosedur juga mengalami peningkatan, terutama pada aspek struktur teks, kaidah kebahasaan, urutan langkah-langkah, dan kejelasan isi teks. Peningkatan tersebut terjadi karena siswa memperoleh pengalaman belajar secara langsung melalui kegiatan proyek sehingga lebih mudah memahami materi pembelajaran.